THE EFFECT OF ECONOMIC LITERATURE, PARENTS' INCOME, AND LIFESTYLE ON THE STUDENTS’ PRODUCTIVE BEHAVIOR AT SMAN 10 PEKANBARU - Rahmadani, Rezky; Sumarno; Gusnardi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This article analyzes the effect of Economic Literacy, Parents' Income, and Lifestyle on Students’ Productive Behavior. The data used are primary data. The data are collected using a questionnaire. The population of the research is 358 students of class X MIPA and IPS, which collected 189 samples. The analytical method used was path analysis. The results indicate that Economic Literacy was proven to have a significant effect on Productive Behavior. In addition, parental income as one of the variables had no effect on Productive Behavior. And Lifestyle had a significant effect on Productive Behavior. Hence, Economic Literacy, Parents' Income, and Lifestyle have an effect on Productive Behavior with a contribution rate of 74.8% overall and the others are influenced by other factors.